Dolomitization in the Upper Paleozoic succession of the north-Ostaninsk field, Nyurolsk Basin, Western Siberia: Implications for hydrocarbon exploration; Marine and Petroleum Geology; Vol. 152 - Garcia Balza A. S. Aura Samid; Krasnoshchekova L. A. Lubov Afanasievna; Asaad I. Sh. Irfan Shaaban; Belozerov V. B. Vladimir Borisovich; Al-Juboury A. I. Ali Ismail (2023, 2023)
Title screen